Особливості призначення судово-медичних експертиз під час розслідування умисних вбивств малолітньої дитини або жінки, яка завідомо для винного перебувала у стані вагітності - Ганжа, Т. В.; Ganzha, T. V. (Науковий вісник Ужгородського національного університету. Серія: Право. - 2017. - Вип. 43, т. 4. - С. 153-157, 2017)
На підставі аналізу наукової літератури та практики органів досудового слідства розглянуті деякі особливості призначення та проведення судово-медичних експертиз під час розслідування умисних вбивств малолітньої дитини або жінки, яка завідомо для винного перебувала у стані вагітності.

Based on the analysis of the scientific literature and the practice of pre-trial investigation bodies, some features of the appointment and conduct of forensic medical examinations in the investigation of the premeditated murders of a young child or woman who was known to be guilty of pregnancy were known. Forensic research plays a very important role in proving a criminal prosecution of the deliberate murder of a young child or a woman who was known to be pregnant for the perpetrator. Unfortunately, in investigative practice, however, sufficient attention is not given to the role of forensic medicine in order to ascertain many evidentiary circumstances during the investigation of this category of criminal proceedings. On the basis of statistical data and practical experience, the classification of forensic examinations is proposed and their contents are disclosed for use in the investigation of this category of criminal proceedings. In the future, it is necessary to create a set of scientifically substantiated forensic recommendations, which will allow the investigator at the initial stage of the investigation to skillfully use the possibilities of special medical knowledge, and in the future can serve as the basis for the formation of a holistic forensic model of the solution of these problems in the context of the method of investigating the deliberate killing of a young child or a woman , which was known to be guilty in the state of pregnancy.

На основании анализа научной литературы и практики органов досудебного следствия рассмотрены некоторые особенности назначения и проведения судебно-медицинских экспертиз при расследовании умышленных убийств малолетнего ребенка или женщины, заведомо для виновного находившейся в состоянии беременности.
Features of the appointment of forensic examinations in the investigation of the deliberate murder of a young child or woman, obviously for the perpetrator was in a state of pregnancy
Ганжа, Т. В. Особливості призначення судово-медичних експертиз під час розслідування умисних вбивств малолітньої дитини або жінки, яка завідомо для винного перебувала у стані вагітності / Т. В. Ганжа // Науковий вісник Ужгородського національного університету. Серія: Право. - 2017. - Вип. 43, т. 4. - С. 153-157.
Keywords: Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; спеціальні знання; судово-медична експертиза; сліди злочину; розслідування умисних вбивств малолітньої дитини або жінки, яка завідомо для винного перебувала у стані вагітності; специальные знания; судебно-медицинская экспертиза; следы преступления; расследование умышленных убийств малолетнего ребенка или женщины, заведомо для виновного находившейся в состоянии беременности; special knowledge; forensic medical examination; traces of a crime; investigation of premeditated murders of a minor child or woman, obviously for the perpetrator who was in a state of pregnancy; Криміналістика. Criminalistics. Криминалистика